Preservation of West Java Culinary Recipe Using Augmented Reality, Photogrammetry, and Storytelling Illustration - Remandhia Mulcki; Fransiska Rachel; Hermanto Laksana (Faculty of Engineering and Technology, Sampoerna University, 2023)
Many traditional culinary recipes from West Java are lost because they are not well-documented; this is a concern for many parties. Losing the recipe means losing the